Circulating tumor cells in patients with breast cancer: monitoring chemotherapy success - Ušiaková, Zuzana; Mikulová, Veronika; Pintérová, Daniela; Brychta, Milan; Valchář, Josef; Kubecová, Martina; Tesařová, Petra; Bobek, Vladimír; Kološtová, Katarína (In vivo (Athens, Greece), 2014)
UNLABELLED: Circulating tumor cells (CTCs) are an independent prognostic factor for patients with metastatic breast cancer (MBC). However, the role of CTCs in early breast cancer management is not yet clearly defined. The aim of this study was to assess the CTC-positivity rate in patients undergoing chemotherapy depending on breast cancer stage in the adjuvant and neoadjuvant setting. We evaluated the ability to confirm therapy response by CTC analysis. PATIENTS AND METHODS: CTCs isolated from blood by means of immunomagnetic separation were further characterized by means of reverse transcriptase - polymerase chain reaction (RT-PCR) for epithelial cell adhesion molecule (EPCAM), mucin 1 (MUC1) and v-erb-b2 avian erythroblastic leukemia viral oncogene homolog 2 (HER2) transcripts with the AdnaTest™. This prospective study included 179 patients; altogether 419 blood samples were evaluated. Patients with primary tumors were divided into neoadjuvant (n=38), and adjuvant (n=100) groups. Forty-one patients with MBC were evaluated under palliative treatment. RESULTS: CTC positivity was described in 35% of patients with early breast cancer without detected metastases before neoadjuvant chemotherapy; similarly, a 26% positivity rate was found in the adjuvant group. In patients with MBC, we detected CTCs in 43% of them. After completing the therapy, the CTC positivity rate decreased to 5% in the neoadjuvant group, to 13% in the adjuvant group and to 12% in the MBC group. CTC positivity after the therapy may classify a subgroup of patients at high risk of developing metastatic disease. This was even true when a patient was evaluated as being CTC-negative before chemotherapy. The multivariate analysis evaluating the correlation of CTC positivity with clinicopathological characteristics such as tumor size, nodal involvement, hormone receptor status, HER2 expression and number of metastatic sites revealed no statistically significant relationships. CONCLUSION: CTC status may have a significant impact on early BC management.
Keywords: breast cancer; Male; nádory prsu u mužů; Neoplasm Grading; Neoplasm Staging; Neoplastic Cells, Circulating; CTC; circulating tumor cells; Breast Neoplasms, Male; Adult; Aged; dospělí; nádorové cirkulující buňky; nádory prsu; senioři; mužské pohlaví; polymerázová řetězová reakce s reverzní transkripcí; Tumor Burden; chemotherapy; lidé; ženské pohlaví; Biomarkers, Tumor; Breast Neoplasms; stupeň nádoru; Humans; Sensitivity and Specificity; senzitivita a specificita; Reverse Transcriptase Polymerase Chain Reaction; tumor burden; Female; lidé středního věku; staging nádorů; nádorové biomarkery; Middle Aged